A preparation method of heterojunction porous liquid and its application

By constructing a heterojunction UIO-66 porous liquid photocatalyst, the problems of poor dispersion and low reaction efficiency in photocatalytic CO2 reduction were solved, and efficient CO2 photocatalytic reduction performance was achieved.

CN117123265BActive Publication Date: 2025-04-11JIANGSU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311088628.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-04-11
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

UIO-66 has poor dispersion in the field of photocatalytic CO2 reduction, its structure is prone to collapse, and its reaction is a heterogeneous reaction, resulting in low catalytic efficiency.

Method used

By introducing UIO-66 porous liquid with hydrophilic groups and in situ coupled with polyionic liquid [M2070][PSS]PIL, a heterojunction porous liquid photocatalyst is constructed to promote its dispersion and stability in water, and the conversion reaction is to a homogeneous reaction.

Benefits of technology

The adsorption capacity of the photocatalyst on CO2 is improved, the recombination of photogenerated electron-hole pairs is inhibited, the enrichment of electrons is promoted, and the photocatalytic reduction performance of CO2 is significantly improved. The yields of CO and CH4 are 30.33 μmol/g/h and 5.62 μmol/g/h, respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117123265B_ABST
    Figure CN117123265B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of environmental and energy material synthesis, and specifically relates to a method for preparing a heterojunction porous liquid and its application. The steps are: using NH2‑UIO‑66‑LV with ligand defects as a carrier, and synthesizing a porous liquid photocatalyst by in-situ coupling with a hydrophilic [M2070][PSS]PIL, which is recorded as NH2‑UIO‑66‑LV PL; the present invention promotes better dispersion of NH2‑UIO‑66‑LV PL in water, thereby facilitating homogeneous photocatalytic CO2 reduction reaction in an aqueous phase without stirring. At the same time, the defects formed and the construction of a Z-type heterojunction effectively inhibit the recombination of photogenerated electron-hole pairs, promote the enrichment of electrons on NH2‑UIO‑66‑LV, and effectively improve the photocatalytic reduction performance of CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental and energy material synthesis, and in particular relates to a preparation method of a heterojunction porous liquid and an application thereof. Background Art

[0002] In recent years, human production and development have led to an increasing amount of CO2 emissions in the atmosphere. Excessive CO2 emissions have caused a series of problems such as global warming, which have had a negative impact on the growth of plants and animals, human survival, and sustainable social and economic development. In order to meet this challenge, photocatalytic CO2 reduction technology has been developed to use solar energy to convert CO2 into fuel or other valuable chemicals. Photocatalytic CO2 reduction technology is of great significance in reducing CO2 concentrations, converting solar energy into green fuels, and realizing the resource utilization of CO2. The research and application of this technology has a potential huge impact on solving the problem of global warming and promoting sustainable development.

[0003] At present, research on UIO-66 in the field of photocatalytic CO2 reduction has made progress. However, UIO-66 cannot be well dispersed in the solution and is prone to structural collapse. Moreover, the reaction of UIO-66 in the liquid phase is a heterogeneous reaction. Heterogeneous reactions usually occur at the interface between two phases, which will lead to lower catalytic efficiency. Therefore, it is of great significance to develop a photocatalyst that has good chemical stability and dispersibility in homogeneous reactions. By constructing a porous liquid based on UIO-66 with hydrophilic groups, it is not only possible to improve the dispersibility and stability of the material in water, but also to convert the photocatalytic CO2 reduction reaction from a heterogeneous reaction to a homogeneous reaction. Improve the adsorption of CO2 by photocatalytic materials. More importantly, better dispersibility can avoid the magnetic stirring process during the experiment, save energy, and further promote sustainable development.

[0004] However, the photocatalytic performance of UIO-66-based porous liquids is currently weak, mainly due to the difficulty in the migration of photogenerated electrons and the serious recombination of electrons and holes, which leads to a slow reaction rate. Therefore, if defects can be introduced into the material, the light absorption ability of the catalyst and the separation ability of photogenerated carriers can be significantly improved, further improving the ability of photocatalytic reduction of CO2. At the same time, in the synthesis process of photocatalytic materials, porous liquids are synthesized by introducing polyionic liquids as liquid ends. Since polyionic liquids are an organic semiconductor with reducing activity, polyionic liquids can construct heterojunctions with UIO-66-based photocatalysts, inhibit the recombination of photogenerated charges, and improve the efficiency of carrier separation, thereby achieving efficient CO2 reduction activity.

[0005] Therefore, the UIO-66 porous liquid photocatalyst with hydrophilic groups is introduced. It has good hydrophilicity and promotes better dispersion of the photocatalyst in water. It can not only improve the adsorption of CO2 by the photocatalyst, but also avoid the magnetic stirring process during the reduction process, which is conducive to promoting sustainable development. At the same time, the defects formed and the construction of the Z-type heterojunction effectively inhibit the recombination of photogenerated electron-hole pairs, promote the enrichment of electrons on the photocatalyst, and enhance the photocatalytic ability of the material. At present, there is no report on heterojunction-type UIO-66-based porous liquid photocatalysts. Summary of the invention

[0006] In order to solve the problem of poor dispersibility of the catalyst in water and easy recombination of photogenerated electron-hole pairs, and realize efficient conversion of CO2, the present invention uses NH2-UIO-66-LV with ligand defects as a carrier, and synthesizes a porous liquid photocatalyst (NH2-UIO-66-LV PL) by in-situ coupling with [M2070][PSS]PIL. Due to the good hydrophilicity of [M2070][PSS]PIL, NH2-UIO-66-LV PL is better dispersed in water, which is conducive to homogeneous photocatalytic CO2 reduction reaction in the aqueous phase without stirring. At the same time, the construction of the Z-type heterojunction formed by NH2-UIO-66-LV and [M2070][PSS]PIL effectively inhibits the recombination of photogenerated electron-hole pairs and promotes the enrichment of electrons on NH2-UIO-66-LV. Therefore, NH2-UIO-66-LV PL has higher photocatalytic CO2 reduction performance than NH2-UIO-66-LV and [M2070][PSS]PIL, and its CO and CH4 yields are 30.33 μmol / g / h and 5.62 μmol / g / h, respectively.

[0007] The present invention also provides a method for preparing a heterojunction porous liquid, which is carried out according to the following steps:

[0008] Step 1: Synthesis of NH2-UIO-66-LV:

[0009] Zirconium tetrachloride and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide, and then formic acid is added as a regulator. After ultrasonic treatment, the obtained mixed solution is transferred to a polytetrafluoroethylene autoclave, and the autoclave is placed in an oven to react at a certain temperature. After the reaction is completed, the product in the autoclave is collected by centrifugation and washed with N,N-dimethylformamide, acetone and ethanol in sequence. The washed product is dried and then calcined in a N2 atmosphere. The calcined product is NH2-UIO-66-LV;

[0010] Step 2: [M2070] [PSS] PIL synthesis:

[0011] The polyetheramine is added to a PSS (poly (4-phenylene sulfonic acid)) solution, and then deionized water is added, and the mixture is fully dissolved by ultrasonic treatment to obtain a mixed solution; finally, the mixed solution is subjected to an oil bath evaporation at a certain temperature, and the solution obtained after evaporation is recorded as [M2070][PSS]PIL;

[0012] Step 3: Synthesis of heterojunction porous liquid (NH2-UIO-66-LV PL):

[0013] First, the NH2-UIO-66-LV prepared in step 1 and the [M2070][PSS]PIL prepared in step 2 were dissolved in deionized water, and ultrasonic treatment was performed to obtain NH2-UIO-66-LV suspension and [M2070][PSS]PIL solution;

[0014] Then, the NH2-UIO-66-LV suspension was added to the [M2070][PSS]PIL solution and stirred evenly to obtain a mixed solution; the mixed solution was then subjected to an oil bath to evaporate the solvent at a certain temperature; the solution obtained after evaporation was vacuum dried at a certain temperature to obtain a heterojunction porous liquid, which was recorded as NH2-UIO-66-LV PL.

[0015] Preferably, in step 1, the usage ratio of zirconium tetrachloride, 2-aminoterephthalic acid, N,N-dimethylformamide and formic acid is: 1 mmol: 1 mmol: 100 mL: 4.3 mL.

[0016] Preferably, in step 1, the ultrasonic treatment time is 30 minutes; the certain temperature condition is 120° C., and the reaction time is 12 hours.

[0017] Preferably, in step 1, the drying is vacuum drying at a temperature of 150° C. and a drying time of 12 h; the calcination temperature is 250° C. and a calcination time is 2 h.

[0018] Preferably, in step 2, the usage ratio of the polyetheramine, PSS solution and deionized water is 18.7 mL:5.5 mL:20 mL; the polyetheramine is polyetheramine M2070; and the mass concentration of the PSS solution is 30%.

[0019] Preferably, in step 2, the ultrasonic time is 120 min; the constant temperature of the oil bath is 80° C., and the evaporation time is 4-8 h.

[0020] Preferably, in step 3, the dosage ratio of NH2-UIO-66-LV and deionized water is 0.2 g:20 mL; the dosage ratio of [M2070][PSS]PIL and deionized water is 1.2 g:20 mL; wherein the volume ratio of NH2-UIO-66-LV suspension and [M2070][PSS]PIL solution when mixed is 1:1.

[0021] Preferably, in step 3, the ultrasonic time is 10-15 min; and the stirring time is 20-30 min.

[0022] Preferably, in step 3, the oil bath temperature is 65° C., and the evaporation time is 4-8 h; the vacuum drying temperature is 65° C., and the drying time is 24 h.

[0023] The heterojunction porous liquid of the present invention uses NH2-UIO-66-LV with ligand defects as a carrier, and synthesizes a porous liquid photocatalyst (NH2-UIO-66-LV PL) by in-situ coupling with [M2070][PSS]PIL. It promotes better dispersion of NH2-UIO-66-LV PL in water, which is beneficial for homogeneous photocatalytic CO2 reduction reaction in water phase without stirring. At the same time, the defects formed and the construction of Z-type heterojunction effectively inhibit the recombination of photogenerated electron-hole pairs, promote the enrichment of electrons on NH2-UIO-66-LV, and effectively improve the photocatalytic reduction performance of CO2.

[0024] The heterojunction porous liquid prepared by the present invention is used for photocatalytic CO2 reduction.

[0025] Beneficial effects of the present invention:

[0026] (1) The heterojunction porous liquid prepared by the present invention forms defects through calcination, which can improve its light absorption and photogenerated carrier separation capabilities, and improve its photocatalytic CO2 reduction ability.

[0027] (2) The heterojunction porous liquid prepared by the present invention introduces a polyionic liquid ([M2070][PSS] PIL) formed by the polymerization of polyetheramine (M2070) and poly (4-phenylene sulfonic acid) solution (PSS) as the liquid end to synthesize the porous liquid. PSS contains hydrophilic sulfonic groups, which can significantly improve the dispersibility and stability of the catalyst in water and enhance the catalyst's adsorption capacity for CO2.

[0028] (3) The heterojunction porous liquid prepared by the present invention retains the abundant micropores of NH2-UIO-66 and the -NH- groups formed inside it, which can promote the adsorption of CO2 by the catalyst.

[0029] (4) The heterojunction porous liquid prepared by the present invention has good hydrophilicity and good dispersibility in water. The presence of the porous liquid transforms the CO2 reduction process from a heterogeneous reaction to a homogeneous reaction. At the same time, there is no need to add magnetic stirring during the CO2 reduction process, which can save energy.

[0030] (5) In the heterojunction porous liquid prepared by the present invention, the PSS added during the polymerization process is an organic semiconductor with reduction activity, which can construct a heterojunction with the UIO-66-based photocatalyst, inhibit the recombination of photogenerated charges, and improve the carrier separation efficiency, thereby achieving efficient CO2 reduction activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Fourier transform infrared spectra of different samples; the samples are [M2070][PSS]PIL, NH2-UIO-66-LV PL, NH2-UIO-66-LV PL (1:2) and NH2-UIO-66-LV.

[0032] Figure 2 Figure 2 is the CO2 adsorption capacity diagram of different samples; the samples are NH2-UIO-66-LV PL and

[2070] [PSS]PIL.

[0033] Figure 3 This is a photo of the fluidity of NH2-UIO-66-LV PL after being placed at room temperature for 240 days.

[0034] Figure 4 Water contact angle diagrams of different samples; a is NH2-UIO-66-LV, b is NH2-UIO-66-LV PL.

[0035] Figure 5 The photocatalytic CO2 reduction yield diagram of different samples; the samples are NH2-UIO-66, NH2-UIO-66-LV, NH2-UIO-66-LV PL and

[2070] [PSS]PIL.

[0036] Figure 6 This is the CO2 reduction cycle experimental diagram of NH2-UIO-66-LV PL.

[0037] Figure 7 EPR spectra of different samples in the dark and after 15 minutes of illumination. DETAILED DESCRIPTION

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terms used in the present invention are only used to describe particular embodiments and are not intended to limit the present invention.

[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0042] Evaluation of photocatalytic reduction of CO2 activity: 10 mg of photocatalyst was mixed in 20 mL of reaction solution containing 18 mL of deionized water and 2 mL of TEOA in a 100 mL quartz glass reactor. Afterwards, the reaction device was purged with pure CO2 gas (purity>99.999%) for 10 minutes, and then vacuum pressurized for more than two times to ensure that all impurities and residual air were completely removed. Before lighting, the reactor was installed on a CEL-SPH2N photocatalytic CO2 reduction reaction system equipped with a 300W xenon lamp to simulate sunlight. Then the xenon lamp was turned on, and the gas was taken every 1 hour. After 5 hours of photoreaction, the xenon lamp was turned off and the mixed solution after the reaction was retained. A gas chromatograph (GC-2030) equipped with a thermal conductivity detector and a flame ionization detector was used to analyze possible gaseous and liquid products, with an Ar carrier gas, a flow rate of 20 mL / min, and a column box temperature of 333K.

[0043] Embodiment 1:

[0044] (1) Synthesis of NH2-UIO-66-LV: 1 mmol of zirconium tetrachloride and 1 mmol of 2-aminoterephthalic acid were dissolved in 100 mL of N,N-dimethylformamide; then, 4.3 mL of formic acid was added as a regulator. After half an hour of ultrasonication, the resulting mixed solution was transferred to a polytetrafluoroethylene autoclave, and the autoclave was placed in an oven and reacted at 120°C for 12 hours. After the reaction, the product in the autoclave was collected by centrifugation and washed with N,N-dimethylformamide, acetone and ethanol in sequence; then, the resulting product was dried at 150°C for 12 hours; thereafter, the dried product was placed in a tubular furnace and calcined at 250°C for 2 hours under a N2 atmosphere to obtain the final product, NH2-UIO-66-LV.

[0045] (2) Synthesis of [M2070][PSS]PIL: 18.7 mL of polyetheramine M2070 was added to 5.5 mL of 30% PSS solution; then 20 mL of deionized water was added and ultrasonicated for 2 hours to fully dissolve the solution to obtain a mixed solution. Finally, the mixed solution was evaporated in an 80°C oil bath for 5 hours. At this time, the volume of the mixed solution no longer decreased, and the obtained solution was [M2070][PSS]PIL;

[0046] (3) Synthesis of heterojunction porous liquid (NH2-UIO-66-LV PL):

[0047] 0.2 g NH2-UIO-66-LV and 1.2 g [M2070][PSS]PIL were dissolved in 20 mL of deionized water, respectively, and ultrasonicated for 10 min to obtain NH2-UIO-66-LV suspension and [M2070][PSS]PIL solution;

[0048] Then, the NH2-UIO-66-LV suspension was added to the [M2070][PSS]PIL solution, and the obtained mixed solution was stirred at room temperature to fully dissolve it. The obtained mixed solution was evaporated in a 65°C oil bath for 4-8 hours, and the evaporated solution was dried in a 65°C vacuum drying oven for 24 hours to obtain a heterojunction UIO-66-based porous liquid photocatalyst, recorded as NH2-UIO-66-LV PL.

[0049] Comparison Materials:

[0050] (4) Preparation of NH2-UIO-66:

[0051] Synthesis of NH2-UIO-66: First, 1 mmol of zirconium tetrachloride and 1 mmol of 2-aminoterephthalic acid were dissolved in 100 mL of N,N-dimethylformamide. After half an hour of ultrasonication, the resulting mixed solution was transferred to a polytetrafluoroethylene autoclave, and the autoclave was placed in an oven and reacted at 120°C for 12 hours. After the reaction, the product in the autoclave was collected by centrifugation and washed with N,N-dimethylformamide, acetone and ethanol in sequence. Finally, the resulting product was dried at 150°C for 12 hours and recorded as NH2-UIO-66.

[0052] (5) NH2-UIO-66-LV PL (1:2)

[0053] 0.2 g NH2-UIO-66-LV and 0.4 g [M2070] [PSS] PIL were dissolved in 20 mL of deionized water and treated by ultrasound for 10 minutes. Then, the NH2-UIO-66-LV suspension was added to the [M2070] [PSS] PIL solution, and the resulting mixed solution was vigorously stirred for half an hour at room temperature to fully dissolve it. Finally, the heterojunction UIO-66-based porous liquid photocatalyst was obtained by evaporation at 65 ° C oil bath for 4-8 hours, and the resulting solution was dried in a vacuum oven at 65 ° C for 24 hours, which was recorded as NH2-UIO-66-LV PL (1:2).

[0054] Figure 1 The following are Fourier transform infrared spectra of different samples. It can be seen that the characteristic peaks of NH2-UIO-66-LV are consistent with the corresponding peaks reported in the published literature (Wang SQ, Wang X, Zhang XY, et al. Effect of the defect modulator and ligand length of metal-organic frameworks on carbon dioxide photoreduction [J]. ACS Applied Materials and Interfaces, 2021, 13: 61578-61586.). In addition, in the FT-IR curve of [M2070][PSS]PIL, the peaks at 2868 cm -1 、1456cm -1 and 1108cm -1 The characteristic peaks of M2070 are at 1035 cm -1 and 1007cm -1 Sulfonic acid groups were detected at the sites, and the appearance of the above characteristic peaks fully demonstrated the successful synthesis of [M2070][PSS]PIL.

[0055] However, due to the large content of the outer liquid end [M2070][PSS]PIL, the FT-IR curves of NH2-UIO-66-LV PL and [M2070][PSS]PIL are basically the same. Therefore, the proportion of the added outer liquid end was adjusted to a smaller amount, and NH2-UIO-66-LV PL (1:2) was synthesized. From its FT-IR curve, it can be seen that its FT-IR curve at 1200 cm -1 -1700cm -1 The characteristic peaks of NH2-UIO-66-LV are basically consistent with those of NH2-UIO-66-LV. At the same time, the peaks at 2868 cm -1 and 1108cm -1 The group at M2070 and 1035cm -1 and 1007cm -1 The above conclusions further prove the successful preparation of NH2-UIO-66-LV PL.

[0056] Figure 2 Figure 2 shows the CO2 adsorption capacity of different samples. The CO2 adsorption capacity of NH2-UIO-66-LV PL is significantly higher than that of the corresponding [M2070][PSS]PIL. NH2-UIO-66-LV PL shows a CO2 absorption capacity of 2.84 mmol / g at 298 K and 4 bar, while the corresponding [M2070][PSS]PIL has an absorption capacity of 1.76 mmol / g. This excellent CO2 absorption capacity reflects that the porous cavity of NH2-UIO-66-LV still exists in NH2-UIO-66-LV PL.

[0057] Figure 3 The photo shows the fluidity of NH2-UIO-66-LV PL after 240 days at room temperature. After 240 days, NH2-UIO-66-LV PL also showed good fluidity, which also proved its excellent stability at room temperature. It is precisely because NH2-UIO-66-LV PL has good fluidity that it can realize the transformation of photocatalytic CO2 reduction reaction from heterogeneous reaction to homogeneous reaction.

[0058] Figure 4The water contact angle diagram of different samples; NH2-UIO-66-LV combined with [M2070][PSS]PIL to form a porous liquid can significantly enhance its hydrophilicity, because [M2070][PSS]PIL contains hydrophilic sulfonic acid groups. At the same time, due to the enhanced hydrophilicity of NH2-UIO-66-LV PL, its dispersibility in water can be improved, thereby promoting its photocatalytic CO2 reduction reaction in the aqueous phase. Through the above research, it can be concluded that [M2070][PSS]PIL provides liquid fluidity for NH2-UIO-66-LVPL. At the same time, due to the hydrophilicity of [M2070][PSS]PIL, the dispersibility of NH2-UIO-66-LV PL in water is improved, and the photocatalytic CO2 reduction reaction in the aqueous phase is transformed from a heterogeneous reaction to a homogeneous reaction, which is beneficial to the contact between CO2 and the catalyst and the dissolution and transmission of CO2 in the liquid phase.

[0059] Figure 5 The photocatalytic CO2 reduction yield of different samples is shown in Figure 2. NH2-UIO-66 exhibits poor photocatalytic performance, with a CO yield of 5.76 μmol / g / h and a CH4 yield of 1.06 μmol / g / h after 5 h of reaction. In contrast, NH2-UIO-66-LV exhibits enhanced photocatalytic activity, with a CO yield of 11.31 μmol / g / h and a CH4 yield of 3.04 μmol / g / h. This may be attributed to the fact that the introduction of defects can shorten the band gap of NH2-UIO-66-LV while enhancing its charge transfer energy. In addition, [M2070][PSS]PIL also has good photocatalytic CO2 reduction activity, with a CO yield of 22.36 μmol / g / h and a CH4 yield of 3.92 μmol / g / h after 5 h of reaction. It is worth noting that by combining NH2-UIO-66-LV with [M2070][PSS]PIL to form a porous liquid, the NH2-UIO-66-LV PL showed excellent CO and CH4 yields of 30.33 μmol / g / h and 5.62 μmol / g / h, respectively. This may be due to the strong electronic coupling between NH2-UIO-66-LV and [M2070][PSS]PIL, which can form a heterojunction and achieve very significant technical results.

[0060] Figure 6 The following are the cyclic test diagrams of different samples. They were continuously illuminated for 25 hours and samples were taken every 5 hours. The results showed that NH2-UIO-66-LV PL showed a stable growth trend in CO and CH4 production during this period, proving that it can maintain good stability in the aqueous phase.

[0061] Figure 7The EPR spectra of different samples in the dark and after 15 minutes of illumination are shown in Figure 1. After 15 minutes of illumination, NH2-UIO-66-LV showed an obviously enhanced EPR signal with a g factor of 2.003, which is due to the Zr 3+ The presence of Zr 4+ Convert to Zr 3+ However, no EPR signal was detected for NH2-UIO-66 under illumination, which means that the charge transfer energy from the organic ligand to the metal cluster in NH2-UIO-66-LV is stronger than that in NH2-UIO-66, which can promote the generation of more electrons and is beneficial to the photocatalytic CO2 reduction reaction. In addition, it is worth noting that after 15 minutes of illumination, NH2-UIO-66-LV PL showed a sharper EPR signal than NH2-UIO-66-LV at the same position, indicating that it generated more electrons in the photocatalytic process to convert Zr 4+ Convert to Zr 3+ According to the composition of the band structures of NH2-UIO-66-LV and [M2070][PSS]PIL, it can be seen that if a type II heterojunction is formed between the two, electrons will transfer from the conduction band of NH2-UIO-66-LV to the conduction band of [M2070][PSS]PIL, and no more electrons will be generated on the conduction band of NH2-UIO-66-LV to transfer Zr 4+ Convert to Zr 3+ Therefore, a Z-type heterostructure is formed between NH2-UIO-66-LV and [M2070][PSS]PIL, and the photogenerated electrons of [M2070][PSS]PIL and the photogenerated holes of NH2-UIO-66-LV are combined with each other, thereby utilizing the photogenerated electrons of NH2-UIO-66-LV to produce an efficient CO2 reduction reaction.

[0062] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a heterojunction porous liquid, characterized in that: The following steps are involved: Step 1: Synthesis of NH2-UIO-66-LV: Zirconium tetrachloride and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide, and then formic acid is added as a regulator. After ultrasonic treatment, the obtained mixed solution is transferred to a polytetrafluoroethylene autoclave, and the autoclave is placed in an oven to react at a certain temperature. After the reaction is completed, the product in the autoclave is collected by centrifugation and washed with N,N-dimethylformamide, acetone and ethanol in sequence. The washed product is dried and then calcined in a N2 atmosphere. The calcined product is NH2-UIO-66-LV; wherein the calcination conditions are: calcination temperature is 250 ℃, and calcination time is 2h; Step 2: [M2070][PSS] PIL synthesis: The polyetheramine is added to the poly(4-phenylene sulfonic acid) solution, and then deionized water is added, and the mixture is fully dissolved by ultrasonic treatment to obtain a mixed solution; finally, the mixed solution is subjected to oil bath evaporation at a certain temperature, and the solution obtained after evaporation is recorded as [M2070][PSS] PIL; Step 3: Synthesis of heterojunction porous liquid: First, the NH2-UIO-66-LV prepared in step 1 and the [M2070][PSS] PIL prepared in step 2 were dissolved in deionized water, and ultrasonic treatment was performed to obtain NH2-UIO-66-LV suspension and [M2070][PSS] PIL solution; Then, the NH2-UIO-66-LV suspension was added to the [M2070][PSS] PIL solution and stirred evenly to obtain a mixed solution; the mixed solution was then subjected to an oil bath to evaporate the solvent at a certain temperature; the solution obtained after evaporation was vacuum dried at a certain temperature to obtain a heterojunction porous liquid, which was recorded as NH2-UIO-66-LV PL.

2. The method for preparing a heterojunction porous liquid according to claim 1, characterized in that: In step 1, the usage ratio of zirconium tetrachloride, 2-aminoterephthalic acid, N,N-dimethylformamide and formic acid is: 1 mmol: 1 mmol: 100 mL: 4.3 mL.

3. The method for preparing a heterojunction porous liquid according to claim 1, characterized in that: In step 1, the ultrasonic treatment time is 30 min; the certain temperature condition is 120 ° C, and the reaction time is 12 h.

4. The method for preparing a heterojunction porous liquid according to claim 1, characterized in that: In step 1, the drying is vacuum drying at a temperature of 150 ° C and a drying time of 12 h.

5. The method for preparing a heterojunction porous liquid according to claim 1, characterized in that: In step 2, the usage ratio of the polyetheramine, the poly(4-phenylene sulfonic acid) solution and the deionized water is 18.7 mL:5.5 mL:20 mL; the polyetheramine is polyetheramine M2070; and the mass concentration of the poly(4-phenylene sulfonic acid) solution is 30%.

6. The method for preparing a heterojunction porous liquid according to claim 1, characterized in that: In step 2, the ultrasonic treatment time is 120 min; the certain temperature of the oil bath is 80 ° C, and the evaporation time is 4-8 h.

7. The method for preparing a heterojunction porous liquid according to claim 1, characterized in that: In step 3, the dosage ratio of NH2-UIO-66-LV and deionized water is 0.2 g:20 mL; the dosage ratio of [M2070][PSS] PIL and deionized water is 1.2 g:20 mL; wherein the volume ratio of NH2-UIO-66-LV suspension and [M2070][PSS] PIL solution when mixed is 1:

1.

8. The method for preparing a heterojunction porous liquid according to claim 1, characterized in that: In step 3, the ultrasonic treatment time is 10-15 min; the stirring time is 20-30 min; the oil bath temperature is 65 ° C, the evaporation time is 4-8 h; the vacuum drying temperature is 65 ° C, and the drying time is 24 h.

9. A heterojunction porous liquid prepared according to the method according to any one of claims 1 to 8.

10. Use of the heterojunction porous liquid according to claim 9 in photocatalytic reduction of CO2.

Citation Information

Patent Citations

  • Preparation method and application of UiO-66-NH2 and RGO interface covalent bond modified photocatalyst

    CN113649074A

  • Preparation method and application of efficient electron transport MOF-based porous liquid photocatalyst

    CN115999644A